Lung ultrasound for etiological diagnosis of pneumonia in the emergency department: correlation with bronchoalveolar lavage results - Pelagatti, Lorenzo; Vannini, Iacopo; Mangani, Francesca; Rossolini, Gian Maria; Volpicelli, Giovanni; Vanni, Simone; Nazerian, Peiman (The Ultrasound Journal, 2025)
Background: Pneumonia is the leading cause of death from infectious diseases worldwide. Lung ultrasound (LUS) is highly accurate for chest infections diagnosis, yet its correlation with causative pathogens remains unclear. Respiratory cultures, combined with molecular techniques represent the gold standard, achieving etiological diagnosis in 90–95% of cases. We compared LUS findings with bronchoalveolar lavage (BAL) sample analyses; to our knowledge, no prior studies have investigated this in the emergency department (ED).Materials and methods: Bronchoalveolar lavage (BAL)-LUS is a prospective observational non-profit study conducted in the ED, aiming to assess whether there is a correlation between the LUS sonographic appearance, assessed blindly across 12 lung fields, and the etiopathogenetic agent of pneumonia (bacterial and viral) detected with molecular syndromic panels (MSPs) and respiratory cultures obtained with BAL.Results: 64 patients were enrolled (mean age 73.3 ± 14.6) with 11 diagnosed as viral pneumonia and 53 as bacterial pneumonia. Bacterial pneumonias were more commonly associated with consolidation (2.9 ± 2.2 vs. 1.5 ± 0.9, p